Monitoring Changes in the Jakarta Flood Disaster with Using Sentinel 2A Imagery - Sulandari, Uci; Mumpuni, Ngesti Sri; Hendrawati, Lulus Suci; Cahyana, Destika (Universitas Ibn Khaldun Bogor, 2024)
DKI Jakarta Province is one of the provinces in Indonesia with a relatively high incidence of flooding since its establishment in the Dutch East Indies era because geomorphologically Jakarta is a floodplain area. On the other hand, land pressure by increasing urbanization in the city of Jakarta results in the increasingly limited availability of decent housing land for the community so that lands that should be water catchment areas and riverbanks are transformed into densely populated flying areas which ultimately reduces water absorption capacity in the Jakarta area. To obtain fast data in identifying flood-affected areas, the technique of identifying the potential extent and distribution of flooding by utilizing the remote sensing NDWI (Normalized Difference Water Index) method and/or using the Modified Normalized Difference Water Index (MNDWI) method from the free data Sentinel 2A satellite can be useful to provide data input to relevant parties in DKI Jakarta Province. Opportunities and constraints The application of NDWI and/or MNDWI techniques will greatly assist mapping activities and identification of the distribution of flood areas as an alternative input to policymakers for action and anticipation of areas with high flood potential. This research is one of the first steps and input to the DKI Jakarta Government in making strategies and roadmaps for flood mitigation in DKI Jakarta.